Strategic aspects of staffing industrial biopharmaceutical companies - A. S. Glazkova; M. V. Duljasova (Путеводитель предпринимателя, 2020)
The role of biotechnology in the development of the Russian economy has been identified. The results ofthe analysis ofthe main trends in the development ofbiopharmaceutics and biomedicine were presented. Options for the development strategies of biopharmaceutical companies, strategies for organizing the processes of staffing industrial biopharmaceutical companies and strategies that determine the characteristics ofthe organization of training and retraining of personnel were proposed, and their relationship was shown.